Novel drug-delivery systems for patients with chronic rhinosinusitis - Albu S (Dove Medical Press, 2012)
Silviu AlbuDepartment of Otolaryngology, University of Medicine and Pharmacy Cluj-Napoca, Cluj-Napoca, RomaniaAbstract: Chronic rhinosinusitis, one of the most common chronic medical complaints in the United States, seems to be increasing in incidence and prevalence, and has a significant impact on quality of life. Topical forms of medical therapy represent an attractive alternative for drug delivery to the nasal cavity and paranasal sinuses. Topical drug delivery has the advantage of directly acting on the site of inflammation, producing a higher concentration at the target site while avoiding systemic side effects. Although considerable research has been undertaken into improving nasal formulations in order to enhance absorption, little attention has so far been directed to upgrading the delivery devices. The aim of this review is to present current knowledge on the novel drug-delivery devices in use in the management of chronic rhinosinusitis patients, and to present the current available knowledge on topical drug penetration into the sinuses using various delivery devices. Additionally, methods used to enhance fluid sinus deposition are presented and the published clinical studies on the results of nebulized antibiotics in the treatment of chronic rhinosinusitis patients are discussed.Keywords: paranasal sinuses, topical therapy, nebulized antibiotics, clinical trials